Julia Brystygierowa wobec tworzenia komunistycznych organizacji polskich w ZSRR (Polski Komitet Narodowy i Centralne Biuro Komunistów Polski) - Stępień, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 2013)
Julia Brystygierowa as a one of the most trusted Polish communist in USSR, was involved in two projects, which had the supervisory character in relation to other Polish communists. The first one was The Polish National Committee, that had the nature of provisional Polish government. Although, she wasn’t in make-up of the Organization Committee for its, she took a part in most of debates concerning with. It is pretty hard to exactly define her importance for whole the organization process, but for sure she was one of „grey eminence”.The second one was Central Bureau Communists of Poland. During production process of Bureau, Julia Brystygierowa was concerned as a member, but lastly she was appointed as a plenipotentiary for the territorial League of Polish Patriots in USSR. As Julia Brystygierowa had seen, that this project won’t be able to achieve intentional meaning, she restricted her part in it, only to confirming identity others communists. For sure, she was mostly concentrated on her tasks in the League of Polish Patriots, than in Bureau.